ANALISIS PUTUSAN MAHKAMAH AGUNG NOMOR 23P/HUM/2024 DAN PUTUSAN MAHKAMAH KONSTITUSI NOMOR 70/PUU-XXII/2024 TERKAIT BATAS USIA CALON KEPALA DAERAH - Hendriawan, Aswin; Mukhlis, Mukhlis; Yusrizal, Yusrizal (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
This research aims to analyze the considerations of Supreme Court judges in Supreme Court Decision Number 23 P/Hum/2024 regarding the Age of Candidates for Regional Head and to find out the implications of Supreme Court decision Number 23 P/Hum/2024 is connected with Constitutional Court decision Number 70/PUU-XXII/2024 related to the Age Limit for Candidates for Regional Heads. limiting the minimum age limit for regional head candidates is considered an obstacle for the younger generation to progress into the world of politics. It becomes even more interesting when two different decisions are made on one issue. The Constitutional Court handed down a decision that was contrary to the Supreme Court's decision, but in line with the Dissenting Opinion expressed with member judges of the Supreme Court. The research method used is a normative juridical research method using the legal and legislative interpretation approach with the data used being secondary data which is analyzed qualitatively so as to produce data in accordance with the problem being studied. Conclusions in this study The Panel of Judges of the Supreme Court used three main frameworks of consideration. First, philosophical-constitutional interpretation, second historical analysis, third substantive principles of justice to protect constitutional rights. This conflict between the Supreme Court and Constitutional Court decisions creates a dualism in legal interpretation that has serious implications.